GEOLOGI DAERAH MINAWEROT DAN SEKITARNYA, KECAMATAN KAUDITAN, KABUPATEN MINAHASA UTARA, SULAWESI UTARA - Luntungan, Paskah Richo; Budiharso, Agus Santoso; Rachmadhan, H.D. (Journal Geological Processes, Risks, and Integrated Spatial Modeling, 2024)
The research location is administratively in North Sulawesi Province, precisely in Kaima Village, Lembean Village, Kaasar Village and Treman Village, Kauditan District, North Minahasa Regency. It is located at the coordinates of 1°16'0"N to 1°17'45"N and 125°01'15"E to 125°03'15"E with an area of 16 km². Along with the improvement of technology and science about the earth along with the increase in the important role of geological maps, the existing updates to the geological map of Minawerot Region, Kauditan District, North Minahasa Regency, North Sulawesi Province with a larger scale of 1:10,000 meals will be able to produce more detailed geological maps to support exploration activities and development programs in the region. In this study, the researcher will identify the geological conditions that develop in the research area which include geomorphological aspects, stratigraphic aspects, geological structure aspects, and geological history aspects so as to produce geological maps, geomorphological maps and stratigraphic columns in the research area. The research method used is a field survey by directly observing the surface geological conditions in the research area which includes geomorphology, stratigraphy and geological structures. The geomorphology of the research area consists of 6 geomorphological units, namely Dissected Volcanic Hills, Volcanic Fluvial Plains, Volcanic Foothills, Eroded Hills, Volcanic Foothills and Lakes. The stratigraphy that developed in the research area consisted of the oldest to the youngest units, namely the Karegesan Andesite Igneous Rock Unit, the Kaima Tuff Breksi Unit, the Tuff Treman Breksi Repeating Unit, the Kaasar Lapili Tuff Unit and the Aluvial Unit. The structure in the research area is only obtained from primary geological structures. After pulling the straightness of the ridge and valley through the DEMNAS, the dominant direction was found, namely the Northwest and Southeast. The geological history that occurred in the research area began with the formation of the Karegesan Andesite Igneous Rock Unit, which was then continued with the deposition of the Tuff Kaima Breksi Unit and then the Tuff Kaima Breksi Repeating Unit. Then it was continued with the deposition of the Kaasar Lapili Tuff Unit and the last one was deposited the Aluvial Unit in the form of loose sediment